Strategies for Sustainability of University-Based Medical Laboratory Sciences Programs. - Behan, Kristina Jackson (Laboratory Medicine, 2021)
The COVID-19 pandemic has taken a major toll on the economy and funding for public education. For that reason, the pandemic has a worrisome effect on the sustainability of university/college based Medical Laboratory Sciences MLS training programs. Stakeholders of university-based MLS programs include university administrators, students, clinical affiliates and faculty. Each group has specific goals and challenges that affect the sustainability of the program. This report details strategies that can be used to satisfy the goals specific to key stakeholders that lead to sustainability. These strategies apply in pandemic times and in the back-to-normal future.